Influence of sex in alcohol‐related liver disease: Pre‐clinical and clinical settings. Issue 2 (3rd March 2023) - Bizzaro, Debora; Becchetti, Chiara; Trapani, Silvia; Lavezzo, Bruna; Zanetto, Alberto; D'Arcangelo, Francesca; Merli, Manuela; Lapenna, Lucia; Invernizzi, Federica; Taliani, Gloria; Burra, Patrizia; ,
Abstract: Alcohol‐related liver disease (ArLD) is a major cause of chronic liver disease globally. Traditionally, ArLD was mostly a concern in men rather than in women; however, such a sex gap is rapidly narrowing due to increasing chronic alcohol consumption among women. Female sex is more vulnerable to the harmful effects of alcohol with a higher risk of progression to cirrhosis and development of associated complications. The relative risk of cirrhosis and liver‐related mortality is significantly higher in women than in men. Our review endeavors to summarize the current knowledge on sex differences in alcohol metabolism, pathogenesis of ArLD, disease progression, indication for liver transplant and pharmacological treatments of ArLD, and provide evidence in support of a sex‐specific management of these patients. Abstract :